Place-responsive Pedagogies in the Anthropocene: attuning with the more-than-human. Issue 6 (3rd June 2021) - Lynch, Jonathan; Mannion, Greg
Abstract: Drawing on New Materialist frameworks for environmental and sustainability education, we extend and deepen our understanding of contemporary place-responsive pedagogies in the light of our human-impacted geological epoch, the Anthropocene, and its allied environmental concerns. Empirically, in a new and original way, we explore the role of the more-than-human in educators' planning and enactment of place-responsive pedagogies. We show that place-responsive pedagogies are derived from ongoing attunements reciprocally made by all participants to each other – educators, learners, and the more-than-human – and between the place of learning and these participants. Findings show that these attunements emerge from socio-environmental processes and features of a place, but this article also shows the critical importance of (i) what educators and learners are able to notice and respond to, (ii) how educators choose to build upon this noticing and response-making, and (iii) how they actively incorporate the agencies of the more-than-human into teaching and learning. Wider implications for researching environmental and sustainability education are considered.